Antitumor effects of novel mAbs against cationic amino acid transporter 1 (CAT1) on human CRC with amplified CAT1 gene. Issue 2 (11th December 2020) - Okita, Kouki; Hara, Yuta; Okura, Hiroshi; Hayashi, Hidemi; Sasaki, Yoko; Masuko, Sachiko; Kitadai, Eri; Masuko, Kazue; Yoshimoto, Soshi; Hayashi, Natsumi; Sugiura, Reiko; Endo, Yuichi; et al.
Abstract: Copy number alterations detected by comparative genomic hybridization (CGH) can lead to the identification of novel cancer‐related genes. We analyzed chromosomal aberrations in a set of 100 human primary colorectal cancers (CRCs) using CGH and found a solute carrier ( SLC) 7A1 gene, which encodes cationic amino acid transporter 1 (CAT1) with 14 putative transmembrane domains, in a chromosome region (13q12.3) with a high frequency of gene amplifications. SLC7A1/CAT1 is a transporter responsible for the uptake of cationic amino acids (arginine, lysine, and ornithine) essential for cellular growth. Microarray and PCR analyses have revealed that mRNA transcribed from CAT1 is overexpressed in more than 70% of human CRC samples, and RNA interference–mediated knockdown of CAT1 inhibited the cell growth of CRCs. Rats were immunized with rat hepatoma cells expressing CAT1 tagged with green fluorescent protein (GFP), and rat splenocytes were fused with mouse myeloma cells. Five rat monoclonal antibodies (mAbs) (CA1 CA5) reacting with HEK293 cells expressing CAT1‐GFP in a GFP expression–dependent manner were selected from established hybridoma clones. Novel anti‐CAT1 mAbs selectively reacted with human CRC tumor tissues compared with adjacent normal tissues according to immuno‐histochemical staining and bound strongly to numerous human cancer cell lines by flow cytometry. Anti‐CAT1 mAbs exhibited internalization activity, antibody‐dependent cellular cytotoxicity, and migration inhibition activity against CRC cell lines. Furthermore, CA2 inhibited the in vivo growth of human HT29 and SW‐C4 CRC tumors in nude mice. This study suggested CAT1 to be a promising target for mAb therapy against CRCs. Abstract : Frequent gene amplification of SLC7A1/CAT1 and increased CAT1 mRNA expression in colorectal cancers (CRC) were demonstrated. Novel anti‐CAT1 monoclonal antibodies (mAbs) were developed, and higher expression of CAT1 protein in CRC and in vivo antitumor effects of mAbs on xenografted CRC cells in nude mice were confirmed. CAT1 may be a promising target for anti‐CRC therapy.